2016
DOI: 10.1080/1554480x.2016.1195741
|View full text |Cite
|
Sign up to set email alerts
|

A critical pedagogy of empathy: making a better world achievable

Abstract: Based on the results of a large-scale study regarding the role of secondary education teachers, we tried to develop an emancipatory teaching programme within the framework of a critical pedagogy of empathy. This teaching strategy is a three-stage process, during which a constant teacher-student interaction, attentive listening and interchange of roles are emphasised, so as to foster empathy. The first stage includes understanding the students' perspectives and giving value to their experiences. When the channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
11
0
3
Order By: Relevance
“…These could range from ‘conventional educational capital’, which might be understood as grades or qualifications, to broader iterations focused on skills and outcomes linked to economic empowerment but which are not well captured by current assessment practice. I assume that Harbourside actively pursues redistribution in relation to this broader iteration; the school’s emphasis on recognition and representation arguably engenders outcomes – such as self-esteem, empathy and group problem-solving skills – that employers are increasingly calling for (see, for example, Bughin et al, 2018), but which it is widely suggested mainstream schooling is failing to inculcate (All-Party Parliamentary Group for Education (APPGfE), 2017; Damianidou and Phtiaka, 2016; Hutchings and Kazmi, 2015). However, due to limitations of space, this section only focuses on data that help assess Harbourside’s redistributive impact in relation to ‘conventional educational capital’.…”
Section: Resultsmentioning
confidence: 99%
“…These could range from ‘conventional educational capital’, which might be understood as grades or qualifications, to broader iterations focused on skills and outcomes linked to economic empowerment but which are not well captured by current assessment practice. I assume that Harbourside actively pursues redistribution in relation to this broader iteration; the school’s emphasis on recognition and representation arguably engenders outcomes – such as self-esteem, empathy and group problem-solving skills – that employers are increasingly calling for (see, for example, Bughin et al, 2018), but which it is widely suggested mainstream schooling is failing to inculcate (All-Party Parliamentary Group for Education (APPGfE), 2017; Damianidou and Phtiaka, 2016; Hutchings and Kazmi, 2015). However, due to limitations of space, this section only focuses on data that help assess Harbourside’s redistributive impact in relation to ‘conventional educational capital’.…”
Section: Resultsmentioning
confidence: 99%
“…A pesar de la dificultad de plantear una pedagogía crítica en el aula, el profesorado tiene ante sí la posibilidad de presentar el conocimiento en forma problemática, de tal manera que el alumnado busque una investigación colectiva hacia el cambio social (COLLINSON, 2012;DAMIANIDOU;PHTIAKA, 2016;ROGERS, 2007).…”
Section: Pedagogía Crítica Y Educación Para El Consumounclassified
“…El modelo educativo de esta pedagogía del consumo consiste en basar el contexto educativo en un modelo de praxis democrática, con un profesorado como agente socializador crítico y constructivo, un intelectual comprometido con la transformación de la sociedad (GIROUX, 1988), más político y pedagógico enfocado en la empatía para poder emanciparse a sí mismo y a sus alumnos, ampliando su enseñanza al establecimiento del igualitarismo (DAMIANIDOU; PHTIAKA, 2016;GIROUX, 2004). Un profesorado dispuesto a conectar la educación y el consumo más allá de la transmisión de contenidos, compartiendo ideas y ejerciendo poder sobre los principios ideológicos que sustentan las prácticas educativas, capaces de construir una vida más humana (GIROUX; MCLAREN, 1989).…”
Section: Pedagogía Crítica Y Educación Para El Consumounclassified
“…As we have already pointed out, in order to achieve this, university education must provide teachers with the necessary tools to understand the latent hidden mechanisms in the school and produce, in turn, a response which guarantees that democratic ideals and social demands will be included in the new school discourse. Despite the difficulty of proposing a critical pedagogy in the classroom, teachers must present knowledge in a problematic way, in such a way that students seek to collectively investigate social change (Collinson, 2012;Damianidou & Phtiaka, 2016;Rogers, 2007). A teacher trained in critical pedagogy will have the tools to break the circle which connects the school of modernity with postmodern society through learned conformity.…”
Section: Some Conclusion: Practices Of Resistance In Schoolsmentioning
confidence: 99%